Pregnancy Outcomes After Human Papillomavirus Vaccination in Periconceptional Period or During Pregnancy: A Systematic Review and Meta-analysis - Anshi Wang; Chang Liu; Yunan Wang; Aihua Yin; Jing Wu; Changbin Zhang; Mingyong Luo; Li Du; Ying Xiong; Xin Zhao; Yanlin Huang (Human Vaccines & Immunotherapeutics, 2020)
Background: National immunization schedules in many countries recommend HPV vaccination for females until the age of 26 years, and thus substantial numbers with reproductive age may be exposed to HPV vaccines. Objective: To assess whether inadvertent HPV vaccine exposures in the periconceptional period or during pregnancy were associated with increased risks for adverse pregnancy outcomes. Search strategy: A search of PubMed, Cochrane Library, China National Knowledge Infrastructure (CNKI), and WanFang databases (until March 31, 2019) was performed. Selection criteria: Studies that assess the risk of adverse pregnancy outcomes in HPV vaccine exposed/unexposed pregnancies were included. The adverse pregnancy outcomes included spontaneous abortion, stillbirth, small for sestational age, preterm birth, and birth defects. Data collection and analysis: The pooled relative risk (RR) was applied for the effect measure of the study. RRs and 95% confidence interval (CI) were measured when the paper did not report the effect. Heterogeneity between studies was assessed using the Cochrane’s Q and I2 statistics. Main results: Of 374 identified citations, 8 met inclusion criteria. Compared with the unexposed pregnancies, HPV vaccine exposed pregnancies were associated with no higher risk for spontaneous abortion (RR, 0.99 [95% CI, 0.90 to 1.08]); stillbirth (RR, 1.16 [95% CI, 0.71 to 1.90]); small for gestational age (RR, 0.96 [95% CI, 0.86 to 1.07]); preterm birth (RR, 1.04 [95% CI, 0.91 to 1.18]); or birth defects (RR, 1.18 [95% CI, 0.97 to 1.43]). Conclusions: Inadvertent bivalent/quadrivalent HPV vaccination during pregnancy was not associated with significantly greater risks of adverse pregnancy outcomes.